ESL learners' enhancement of standard english accent among Khotimul Quran of a primary school students in Malaysia - Kamariah, Yunus; Nurul Atasha, Mohd Nordin (2020)
CEFR (Common European Framework of Reference for Languages) is a new syllabus for English language subject of Malaysia primary school students. However, none of pronunciation elements involve the stress, rhythm and intonation have been emphasized to accomplish Standard English Accent. The issue is that, Malaysian primary school students do not apply correct stress and intonation while speaking and reading Standard English. Therefore, this study aims to identify the use of stress, rhythm and intonation applied in their spoken English words by both groups. The researcher had choose 15 Khotimul Quran students as the experimental group, whose background had complete reciting Quran for the whole 30 Juz and 15 common students as the control group from Sekolah Kebangsaan Pusat Air Tawar, Johor as the unit of analysis. The researcher uses semi-structured interview, observation and focus group discussion to triangulate the data. Pilot data analysis of the responses had shown a strong correlation between speaking Standard accent with correct stress, rhythm and intonation among the Khotimul Quran. Based on this results, the researcher expects the experimental group those who have Quranic-phonological background achieves higher percentages of accurateness of speaking Standard English accent compares to the control group.